Unlocking the antioxidant potential of Malaysian traditional salad (ulam) as a halal natural carotenoid source - Mohd Hatta, Farah Ayuni; Mat Ali, Qurratu Aini; Othman, Rashidi; Mohd Kashim, Mohd Izhar Ariff; Ramya, Razanah; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie (Malaysian Institute of Chemistry, 2024)
Excessive free radicals in human bodies are a leading cause of skin ageing and serious illnesses. To combat this issue, there is an increased interest in investigating dietary sources that are rich in antioxidants. The traditional Malaysian salad, known as ulam, has been used for decades by the locals for its potentials healing properties. However, there is a lack of scientific evidence regarding the antioxidant properties and carotenoid content of these ulam species, despite their high availability and economic feasibility. Therefore, this study aimed to investigate the potential of 40 different ulam species as sources of carotenoids and antioxidants. Our findings revealed that ulam is a rich, halal source of carotenoids and possesses significant antioxidant properties. Carotenoid levels differ among ulam species, with some exhibiting higher levels than others. The results showed that ulam can be recognised as a halal natural source of carotenoids for the food, cosmetic, and pharmaceutical industries. Ulam availability and economic feasibility make it a sustainable option for halal antioxidant supplementation. The findings of this study will benefit manufacturers, scientists, consumers, and others, with the potential to unlock the antioxidant potential of ulam and draw further attention to its nutritional and therapeutic benefits.